Analysis of the Effectiveness of the Pricing Policy of the Organization: Practical Aspect (on the Example of JSC “Verkhnebakansky Cement Plant”) - I. P. Kovaleva (Учёт. Анализ. Аудит, 2019)
The theoretical concepts of evaluating the effectiveness of the pricing policy of an organization are fairly fully represented in both Russian and foreign sources. However, the practical aspects of this issue, often related to the specifics of the activities of each individual domestic enterprise, its financial and pricing policies, have their own characteristics. This is especially true in conditions of instability, when commercial organizations are forced to look for various ways and methods to optimize their activities. One of such methods is the study of the financial results of the organization’s activities when applying various pricing tactics, for example, using discounts and without them for regular customers. To achieve this goal, it is recommended to conduct a variety of analytical procedures based on accounting data. At the same time, projected financial results for the enterprise can be calculated and the main directions for optimizing its pricing policy will be selected. For example, improving: pricing in terms of upgrading information support; pricing process through the use of new methods in the field of planning and forecasting prices; pricing policy by changing its main elements such as methods, strategies and tactics. Taking into account the specifics of the organization’s activities, various directions and tools are offered for using these methods in pricing. For the cement industry in particular one of the ways to improve the efficiency of the pricing process can be offering retail sales at the price of the main price list. Thus, by analyzing the pricing policy of an enterprise and making conclusions about the influence of various factors on its effectiveness, it is possible to significantly improve the organization’s activities, having a positive effect on its financial results, both in the current period and in the future.